ANALYSIS OF THE DEVELOPMENT OF CULINARY TOURISM DESTINATION IN TANJUNGPINANG CITY THROUGH SEMPRONG CAKE FESTIVAL - Rini, Rosie Oktavia Puspita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2021)
Full support of tourist activities in each area to accelerate in achieving the target of tourist visit is expected for the tourism advancement in each region. Tanjungpinang is one of the three main gates in Riau Islands. The city of Tanjungpinang prepares various events and festivals to support the growth of tourists visit. Tourists now demand a dining experience that is not only a process of fulfilling the needs felt by the taste buds, but also the other four senses. Focusing on tourists demands, the purpose of this research is to find out the development of culinary tourism destinations through one of the semprong cake festivals held in Tanjungpinang city. Research Method use Qualitative Descriptive Based on the result of the study, organizer was very successful in making an interesting concept. However, the limitations of the organizer in conducting the festival resulted in not achieving the aims of the festival. Thus, the readiness to develop a culinary tourism destination become unfulfilled. In this case, it is necessary to take a strategic view of creating experience with synergy through the 4A approach, that are Attractions, Access, Amenities and Assisting Facilities. Keywords:Tourism, Culinary Tourism, Festival